Integrated management of viral diseases of bittergourd (momordica charantia L.) - Radhika N S (Department of Plant Pathology, College of Agriculture, 2018)
The present research work entitled ‘Integrated management of viral diseases of bitter gourd (Momordica charantia L.) was carried out in the College of Agriculture, Vellayani during 2014-2017, with the objectives to study the occurrence and distribution of viruses in bitter gourd in Thiruvananthapuram, Idukki and Palakkad, immunomolecular characterization of the viruses, and screening of antiviral chemicals, antiviral principles of animal, plant and microbial origin for the management of the disease. In the suvey conducted at five locations in Thiruvanaanthapuram district, Pappanchani area recorded highest incidence of viral disease (60%) while highest Vulnerability Index (V.I) was recorded from Vellayani (56.00). In Idukki district, six major bitter gourd cultivating areas were surveyed among which Rajakumary area recorded the highest disease incidence (100%) and V.I (82.00). In Palakkad district, five locations were surveyed, among which panackatri and Thekkepotta recorded highest disease incidence of 88% and highest V.I (69.00). The major insects associated with the crop were whitefly (Bemisia tabaci (Genadius) with an incidence of 10-25%, aphids (Aphis gossypii glover) with an incidence of 10-40%, Jassids (Empoasca (Empoasca) motti Pruthi) with an incidence of 10-30% and mites with an incidence of 10-50%. Phyllody and little leaf symtoms (20% incidence) were also recorded in bittetgourd form Rajakumary and Rajakkad areas in Idukki. Flat limb and multiple proliferation of shoot tip were observed at many fields in Idukki. Symptoms associated with the disease include yellow mottle, mosaic,blistering, leaf curl and reduction in leaf size. Yellow mosaic and blistering is seen in severe infection finally leading to stunting of the plant, reduced flowering an fruiting and hairyness on stem. Mechanical transmission of the virus on Datura stramonium produced yellow lacal lesions indicating the presenceof Bean Golden mosaic virus (Begomo) in the infected leaf extract. This leaf extract also produced local lesions on othe indicator hosts like Chenopodium amaranticolor and Gomphrena globosa indicating the presence of Cucumber mosaic virus (CMV) or Potato virus Y (PVY). The viruses were transmitted by whiteflies (20%) and aphids (30%) from infected bittetgourd plants to healthy seedlings. Whiteflies (Bemisia tabaci Gennadius)) and aphids (Aphis gossypii Glover) are the vectors of the respective viruses Wedge grafting diseases scion on to 3-5 leaf stage healthy seedling of bittergourd produced symptoms of infection within ten days. KAU varieties Preethi and Priyanka were found to be susceptible to infection with preethi expressing a V.I of 70.80 and Priyanka expressing a V.I of 62.50 respectively. Ensyme linked immunosorbent assay (ELISA) and Dot immunobinding assay (DIBA) revealed the presence of three viruses belonging to Begomo, CMV and PVY group causing an mixed infection in bittergourd. The presence of all the three viruses were also confirmed in electron micrograph, Begomovirus as twin particles of size 18-20 X 30nm,CMVas single particles of 18nm and PVY as lonog flexuous rod of size 750nm. PCR amplification of coat protein gene (cp gene) of virus isolates from all the three districts yielded an amplicon of size approximately equal to 570 bp. Idukki and Palakkad isolates showed 94% identity to Tomato leaf Curl Virus isolate TNUDU BGI Coat Protein (AVI) gene while Trivandrum isolate showed 95% identity to Tomato leaf Curl Virus isolate TNPDU BG4 Coat Protein (AV1) gene . Phylogenetic tree constructed using multiple sequence alignment programme showed close relation between Begomo viruses identified in bittergourd from different districts. Studies on defense related enzymes such as peroxidase (PO), polyphenol oxidase (PPO) and phenyl alanine ammonialyase PAL) showed significant activity of PO and PPO in diseased plants than in healthy plants and the activity was on par in healthy and diseased for PAL. Protien profile of healthy and diseased at different days after virus inoculation through grafting indicated the production of novel proteins in diseased. There was no difference in the native profile of peroxidase in healthy and diseased at 15 days after virus inoculation. An additional isozyme band with a Rm value of 0.5 was observed in diseased at 45 days after virus inoculation. Management of the disease with antiviral chemicals and antiviral principles of plant, animal and microbial origin was undertaken as pot culture studies with pre and post inoculation of treatments. Twelve treatments with three replications each were laid out in completely randomized design for the evaluation. The treatments included Aspirin at two levels of 100 and 150 ppm, Salicylic acid (SA) at two levels of 100 and 150 ppm and Acibenzolar S methyl (ASM) at 50 and 75 ppm concentration, and two commercial formulations viz., Perfect and virus –Ex at 0.5 and 1.0 ml concentrations. The treatments were applied three times at 10 days interval. Pre application of thrice sprapying of Acibenzolar S methyl (ASM), 75 ppm concentration (V.I-35.00) at ten days interval was statistically significant over other treatments followed by ASM-50 ppm (V.I-41.33). Post application of antiviral chemicals also showed a statistically significant effect of three times spraying ASM-50 ppm(V.I-25.00) at ten days interval followed by spraying of Virus Ex 1ml L-1 (V<I-47.25), aspirin 150 ppm (48.09), followd by Salicylic acid (SA)-100 ppm (V.I-51.27). Pre and post applaication of antiviral principles of plant, animal and microbial origin was carried out thrice at ten days interval. Pre application of papaya leaf extract (10%) was Stsatistically significant (V.I-20.75) followed by bougainvillea leaf extract (10%)(V.I-28.94). Pseidpmonas fluorescens talc based formulation (2%) was the next best with V.I of 46.07. Post application of bougainvillea leaf extract(10%) (V.I-21.67) and papaya leaf extract (10%) (V.I-23.33)were on par followed by Pseudomonas fluorescens talc based formulation (@%) (V.I-38.33) and buttermilk (three times dilution of curd) (V.I-36.67). Protein profile done after the application of different treatments also revealed the presence of novel proteins. The best eight treatments with control was laid out as Randomised Block Design at the Instructional Farm, College of Agriculture, Vellayani during February to May 2017 as a field trial to study the effect of treatments on natural incidence of the viruses in the susceptible variety Preethi. The treatment, three sprays of ASM-50 ppm (V.I-28.33) at ten days interval ws on par with buttermilk (Three times dilution of curd) (V.I-39.16). Yield was also significantly high in ASM-50 ppm (437g plant-1) followed by Pseudomonas fluorescens talc based formulation (2%) (233 g plant-1)among the treatments.